The Role of Social Values and Ethics in Designing Privacy-Preserving Big Data Systems - Irfan Rashid (Universitas Komputer Indonesia, 2025)
The adoption of big data technologies globally and in Pakistan raises critical user privacy and ethical concerns. While technical advancements enable extensive data analysis, integrating social values into system design remains insufficiently addressed. This article examines the role of ethical frameworks—prioritizing autonomy, equity, and transparency—in developing robust data protection mechanisms. We analyze current privacy-preserving techniques, highlight underlying ethical gaps, and propose an integrated design approach that aligns technical solutions with social norms. Furthermore, visual analyses compare data protection frameworks and privacy violation trends within the digital landscape. Ultimately, we recommend that designers and policymakers embed these ethical values into system architectures to ensure sustainable, user-centric data protection.